Factors Influencing Consumer Choices and Organic Food Production in Haryana: Insights from Farmers - Yadav, Ekta; Goyal, Megha; Ghalawat, Suman; Malik, Joginder Singh; Devi, Monika; Mehala, Vinay (Indian Journal of Extension Education, 2024)
The study examined consumer behaviour dynamics in Haryana related to organic food purchases and forecasted production, in 2023-2024. The research employed area sampling; representing four districts based on organic food store availability, and surveyed 300 consumers during 2024. Three key factors influencing purchasing decisions were identified: benefits of organic food, characteristics of organic food, and promotional tools. The Benefits of organic food, explaining 30.461 per cent of the variance, was the most significant, emphasizing health advantage, environmental protection, and trust in organic labels. Characteristics of organic food contributed 19.197 per cent of the variance, focusing on quality, affordability, and chemical-free production. Promotional tools; accounting for 14.172 per cent, highlighted discounts, taste, and online marketing. These factors collectively explained 63.830% of consumer decision-making, with health and environmental benefits emerging as primary motivators. The study forecasted organic food production in Haryana from 2011-12 to 2022-23 using polynomial regression analysis, with a moderate model fit (R² = 0.60). The findings revealed significant production fluctuations due to external factors, suggesting the need for continued research to improve forecast accuracy.
Keywords: Farmers; Production; Organic farming; Forecasting; Consumer; Polynomial regression